The Transformation of Moral Education Through Strategic Management Based on Islamic Values - M. Abdurohman; Ahmad Khori (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study examines the strategies and implementation of Islamic character education at Madrasah Aliyah Asshidiqiyah Karawang, with a focus on integrating Islamic values into the curriculum, teaching methods, and school culture. Using a qualitative case study approach, data were collected through observations, in-depth interviews with teachers and students, and document analysis. The findings reveal a holistic approach that integrates Islamic values into both academic and extracurricular activities, such as project-based learning, congregational prayers, dhikr (remembrance), and social service programs. Teachers serve as primary role models, supported by parental involvement and school policies. Despite challenges like limited teacher training, external environmental influences, and less-than-optimal parental participation, the character education program significantly improved students’ discipline, honesty, and social responsibility. The study concludes that Islamic character education is effective when implemented comprehensively and collaboratively among schools, teachers, and families. It recommends enhancing teacher training, strengthening community partnerships, and conducting ongoing evaluations to ensure the program’s sustainability and success.